RECOVERY OF GOLD AND SILVER FROM GOLD MINE TAILINGS - Erdenebold, Urtnasan; Jei-Pil, Wang (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
Gold mine tailings may contain relatively high concentrations of valuable metals such as iron, copper and zinc and occasionally, even precious metals such as gold and silver. The Au and Ag concentrations in the tailings from gold mining in Jeonnam Province are 110 mg/kg and 3 380 mg/kg, respectively. Their major components are SiO2, Fe2O3 and Al2O3, but they also contain reactive sulphide minerals such as pyrite. We used high temperature smelting and additives to dissolve Au and Ag from the gold mine tailings into the molten copper. Gold greatly dissolved (82 mg/kg Au in the molten copper) at 1600 °С under a CaO/SiO2 ratio of 1.25, suggesting the increase in the dissolution of gold with the decreasing viscosity of the molten tailings at high temperatures.